Incidence of acute tonsillitis in the sentinel practice network in 1998. - Simões, José Augusto (2002)
Objective: To assess the incidence of acute tonsillitis in the population under surveillance by the Sentinel Network in 1998 Type of study: Observational, descriptive. Setting: Portuguese Health Centers where general practitioners belonging to the Sentinel Network are working. Population: Patients registered with the participating general practitioners. Methods: During 1998 all new cases of acute tonsillitis were recorded and notified. Notifications included informwtion on the symptoms and signs refered to in the ICHPPC-2 Defined. These data were used to calculate incidence rates and 95% confidence intervals of acute tonsillitis in the population under surveillance. Rates were compared using Chi-square and Fishers exact test. Results: 1536 cases were notified (641 males and 895 females), from a total population under surveillance of 138.221 (65,716 males and 72,505 females). The acute tonsillitis incidence rate found was 1111.3/105, with 975.4/105 for males and 1234.4/105 for females. Symptoms and signs more often found were «sore throat» in 96% of cases, «fever» in 92%, «tonsils redder than the pharynx posterior wall» in 87.9%, «swollen tonsils» in 86%, «pus on the tonsils» in 79,7% and «swollen regional glands» in 54.9% of cases. In 98.1% of cases an antibiotic was prescribed, and in 52,4% of cases the antibiotic was started at the second day of fever. The most prescribed antibiotic was the association amoxycillin/clavulamic acid (25.8%) followed by penicillin (23.2%), amoxicillin (17.5%) and clarithromycin (8.4%). Conclusions: This study allowed the estimation of an incidence rate in the population under observation of 1111.3/105, (975.4/105 in males and 1234.4/105 in females). It was noted that the presence of pus on the tonsils seems to be associated with a higher frequency of antibiotic prescribing (99.4% of cases with pus, versus 17.4% of cases without) which is in accordance with the empirical approach of treating tonsillitis with exsudate with an antibiotic. A new study including the collection of exsudate specimens for bacteriological and virological analysis should be performed in subsequent years.